Sexual Harassment and the Developing Sense of Self Among Adolescent Girls - Berman, Helene; Izumi, Janet; Arnold, Carrie Traher (Canadian Journal of Counselling and Psychotherapy, 2007)
Girls encounter various forms of violence as a common part of their everyday lives. In recognition of the obstacles and challenges faced by this population, a multiphased national action study was conducted by the Alliance of Five Research Centres on Violence*. The primary focus was to examine how violence becomes normalized in the lives of girls. In this paper, we present findings from the Ontario component of the project with particular attention to sexual harassment as it is experienced and understood by girls. Findings reveal that sexual harassment occurs in a highly public manner; it is supported and condoned in subtle and explicit ways; and through its enactment, girls are continually silenced and their sense of selves diminished. Implications for counselors working with this population, and strategies for encouraging and affirming healthy resistance, are discussed.*The Alliance of Five Research Centres on Violence consists of: The FREDA Centre in Vancouver, BC; the RESOLVE Centre in Winnipeg, MB, Saskatoon, SK and Calgary, AL; the Centre for Research on Violence Against Women and Children in London, ON; the Muriel McQueen Fergusson Centre in Fredericton, NB; and the CRI-VIFF in Sainte-Foy, QC.